Legal analysis of implementation of the traffic accident monitoring system - Atamanenko, Yuliia Y.; Merdova, Olga M.; Martsenyshyn, Yurii I.; Tsurkan, Oleksii P.; Chebotar, Stanislav O. (Journal of the University of Zulia, 2022)
Purpose. The study aims to establish positive changes after the introduction of traffic accident monitoring systems implemented by government agencies in China, India, Germany, the United States, the United Kingdom, Finland, Beijing and Sweden. Methods. The research was carried out in stages, based on the logical presentation of the material. The following methods were implemented in the study: direct observation, comparison and analysis of the content and the form of advanced traffic accident monitoring systems. Results. The study of international best practices and experiments about the implementation of various options for traffic accident monitoring systems gave preference to an intelligent system. A study conducted in the United States, India and Portugal shows the effectiveness of different approaches to use mobile applications on smartphones to transmit reliable information to the traffic accident registration system. Accident data collection should be standardized and structured, and police officers should benefit from the statistical reports they complete for each traffic accident.